PENGARUH BRAIN GYM TERHADAP KECEMASAN DAN KOGNITIF MENOPAUSE: LITERATURE REVIEW - Nur Baety Sa’diyah; Ema Wahyu Ningrum; Siti Haniyah (Bajang Institute, 2022)
Psychological changes that occur, namely the decline in intellectual which includes perception, cognitive abilities, memory and learning at an advanced age makes them difficult to understand and interact. Pathologically a decrease in the number of cholinergic neurons will cause a decrease in the neurotransmitter acetylcholine, causing cognitive and behavioral disorders. Non-pharmacological therapy needs to be applied to delay cognitive decline by implementing healthy behavior and doing brain stimulation as early as possible to train the brain's ability to work. The selection of data sources is carried out by taking into account matters related to the authenticity of the writing, objectivity, and contribution to the research. Based on the results of a lietarure review of 10 journals, the results of the review that the author did found that the factors that influence brain exercise on anxiety and cognitive function of menopause are age, and gender. If menopausal women regularly do brain exercise.